The Outcomes of Ethics Education to Medical Students Based on Moral Reasoning Models - Athar Omid; Nikoo Yammani; Peyman Adibi (مجله ایرانی آموزش در علوم پزشکی, 2014)
Introduction: For years, the importance of medical ethics education in medical schools has been emphasized but there is no consensus over learning goals yet. This study aimed to investigate the learning outcomes of medical ethics education based on models of moral reasoning. Methods: This study is a review using proper keywords in databases such as Medline, Web of Science, Scoupus, and Eric limiting the results to papers published from 1990 to 2012 which resulted in finding61 articles. Seven articles related to learning objectives and 12 articles related to the model were investigated. Results: Researchers have different views on learning objectives of medical ethics education. Some believe that the goal of ethics education is to train virtuous physicians. Others believe that the more practical and measurable goal is moral reasoning skills. Showing the cognitive and attitudinal elements of an ethical behavior, however, Rest Model postulates the four components for ethical behavior to flourish. Conclusion: For teaching ethics education, skills such as emotional control, tolerance of ambiguity for multiple perspectives, and empathy in difficult situations should be taught in addition to teaching ethical principles. Moreover, appropriate environments regarding role modeling and encouraging ethical values must be provided for learners. Providing reflective opportunities also will bring insight on ethical codes that results in increasing moral commitment.